Studi Residu Antibiotika dan Kualitas Mikrobiologi Telur Ayam Konsumsi yang Beredar di Kota Administrasi Jakarta Timur - Anton; Taufik, E.; Wulandari, Z. (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2020)
Chicken eggs are fairly high in nutritional content, especially in proteins. Usually, antibiotics are used indisease prevention and treatment program at the layer chicken farms. The use of antibiotics are still notaccording to the direction of use. Egg production is also susceptible to bacterial contamination. Therefore,the objective of this study was to analyze the presence of kanamycin residue, the microbiological quality,and to evaluate potential risk factors associated with the microbiological quality of chicken eggs in theadministration city of East Jakarta. The samples were 100 eggs taken from 21 traditional markets and4 supermarkets in the administration city of East Jakarta. Kanamycin residue tested using bioassaymethod based on SNI 7424: 2008 and the microbiological quality method used based on SNI 3926: 2008.Data were analyzed using descriptive analysis univariate Chi-Square test to determine the effect ofpotential risk factors on the quality of microbiological quality and logistic regression models to analyzethe effect of potential risk factors without looking at the interaction of other factors. The results showedthat kanamycin residues were detected in 26.19% of eggs from traditional markets and 31.25% eggsfrom supermarkets in the administration city of East Jakarta. The median value of TPC, coliform andE.coli were 0.7 log cfu/g, 1.5 MPN/g, and 1.5 MPN/g, respectively, whilst Salmonella sp test was negative.It can be concluded that kanamycin residues still found in the markets and the microbiological qualitywere below the maximum contamination limit based on SNI 3926:2008 and egg cleanness was a riskfactor for coliform contamination.